Attentional Bias Modification Training in Virtual Reality: Evaluation of User Experience - María Teresa Mendoza-Medialdea; Ana Carballo-Laza; Mariarca Ascione; Franck-Alexandre Meschberger-Annweiler; Bruno Porras-Garcia; Marta Ferrer-Garcia; José Gutiérrez-Maldonado (Applied Sciences, 2023)
Recent technological advances have paved the way for incorporating virtual reality (VR) into attentional bias modification training (ABMT) for the treatment of eating disorders. An important consideration in this therapeutic approach is ensuring the ease and comfort of users of the hardware and software, preventing them from becoming additional obstacles during treatment. To assess this, 68 healthy participants engaged in an ABMT experiment aimed at evaluating various factors, including usability as well as the participants’ comfort while using the VR equipment, task-induced fatigue, and attitudes towards the technology. Our results indicated a favorable usability level for the ABMT proposed in this study. While their discomfort, anxiety, and fatigue increased during the task, these did not significantly impact its execution. However, heightened anxiety and fatigue were linked to lower evaluations of software usability. Other variables considered in the experiment did not notably affect the task.